eIF4G1 N-terminal intrinsically disordered domain is a multi-docking station for RNA, Pab1, Pub1, and self-assembly - Chaves-Arquero, Belén; Martínez-Lumbreras, Santiago; Sibille, Nathalie; Camero, Sergio; Bernadó, Pau; Jiménez, M. Ángeles; Zorrilla, Silvia; Pérez-Cañadillas, José Manuel (Frontiers in Molecular Biosciences, 2022)
Yeast eIF4G1 interacts with RNA binding proteins (RBPs) like Pab1 and Pub1 affecting its function in translation initiation and stress granules formation. We present an NMR and SAXS study of the N-terminal intrinsically disordered region of eIF4G1 (residues 1–249) and its interactions with Pub1, Pab1 and RNA. The conformational ensemble of eIF4G11-249 shows an α-helix within the BOX3 conserved element and a dynamic network of fuzzy π-π and π-cation interactions involving arginine and aromatic residues. The Pab1 RRM2 domain interacts with eIF4G1 BOX3, the canonical interaction site, but also with BOX2, a conserved element of unknown function to date. The RNA1 region interacts with RNA through a new RNA interaction motif and with the Pub1 RRM3 domain. This later also interacts with eIF4G1 BOX1 modulating its intrinsic self-assembly properties. The description of the biomolecular interactions involving eIF4G1 to the residue detail increases our knowledge about biological processes involving this key translation initiation factor.